Results of Endoscopic Dacryocystorhinostomy under Local Anesthesia with Minimal Sedation - Woong Chul Choi; Ji-Sun Paik; Sang Hee Doh (Journal of Ophthalmology)
Purpose. We evaluated the tolerability and efficacy of endoscopic dacryocystorhinostomy (Endo-DCR) in patients treated in the leaning position and under local anesthesia with minimal sedation (LAS). Study Design. Questionnaire to determine subjective success of Endo-DCR. Methods. From May 2013 to August 2014, a total of 95 eyes with epiphora presented to the Myoung Eye Plastic Surgery Clinic in Seoul, Korea, and were treated with Endo-DCR under LAS. Three nerve blocks were administered to achieve local anesthesia. Postoperatively, the wound site was packed with Nasopore to control bleeding and promote wound healing. Outcome measures included a patient questionnaire completed on postoperative day 7 to evaluate intraoperative and postoperative pain based on the VAS (0 to 10). Results. Mean intraoperative and postoperative pain scores were 1.03 and 1.64, respectively, for 95 eyes. Of the 95 eyes treated, the patients in 82 eyes (86.31%) reported that they would prefer LAS over GA for a repeat Endo-DCR. The subjective and objective surgical success rates were 90.14% and 95.77%, respectively. Conclusions. Endo-DCR carried out under LAS with the patient in the leaning position is more useful, efficient, and feasible than Endo-DCR performed under GA with the patient in the supine position.